EXPLORING SCULPTORS' EMOTIONAL INTELLIGENCE AND JOB STRESS CREATIVITY, EMOTIONAL MANAGEMENT, AND OCCUPATIONAL OBSTACLES - P., Arul Seelan; S., David (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper investigates the relationship between emotional intelligence (EI) and work stress among sculptors, exploring how emotional competencies influence occupational well-being in the context of artistic creativity. Utilizing a mixed-methods approach, quantitative surveys and qualitative interviews were conducted with a sample of sculptors. The realm of artistic production, particularly sculpture, provides a stimulating setting for investigating the complex relationship between emotional intelligence (EI), occupational stress, and the creative process. This project will conduct a complex investigation into the emotional dynamics experienced by sculptors, with the goal of determining how their emotional intelligence effects their ability to negotiate the inherent vocational hurdles while sustaining artistic life. Drawing on known ideas of emotional intelligence and stress management, this study aims to provide a more nuanced understanding of the emotional terrain that sculptors navigate. Using a mixed-methods approach, quantitative surveys and qualitative interviews were done with a group of experienced sculptors, providing a thorough analysis of their emotional experiences in relation to their professional endeavors. Emergent motifs were uncovered using thematic analysis, providing valuable insights into the complex emotional landscapes of sculptors. This study adds to the growing literature on emotional intelligence in the arts by providing a contextualized knowledge of the consequences for sculptors' professional well-being. These findings have ramifications beyond academic discourse, informing practical interventions targeted at assisting sculptors in growing emotional resilience, creating a positive work environment, and sustaining their creative energy. Ultimately, this study demonstrates the profound interaction of creativity, emotional intelligence, and occupational constraints in the field of sculptural artwork.